Improving Tobacco Cessation Rates Using Inline Clinical Decision Support - Drake, Lauren A.; Suresh, Krithika; Chrastil, Hillary; Lewis, Carmen L.; Altman, Richard L. (Applied Clinical Informatics, 2022)
Background Tobacco use is a significant cause of morbidity and mortality in the United States. Even brief advice from a clinician can significantly influence cessation rates among tobacco users, but clinicians often miss opportunities to provide this simple intervention.Objectives The intent of this quality improvement project was to increase tobacco cessation among tobacco users by nudging clinicians using a clinical decision support (CDS) tool.Methods We developed a CDS tool using principles of user-centered design and the CDS Five Rights to dynamically insert actionable information about current tobacco users into the Assessment and Plan section of clinicians' notes. We conducted a retrospective analysis of patients at four primary care practices in the Denver Metro area evaluating the impact of the CDS tool on time to tobacco cessation. A multivariable Cox proportional-hazards model was used in this determination. Kaplan–Meier curves were used to estimate tobacco cessation probabilities at 90, 180, and 365 days.Results We analyzed 5,644 patients with a median age of 45 years, most of whom lived in an urban location (99.5%) and the majority of whom were males (60%). The median follow-up time for patients was 16 months. After adjustment for age, gender, practice site, and patient location (rural, urban), the intervention group had significantly greater risk of tobacco cessation compared to those in the control group (hazard ratio: 1.22, 95% confidence interval: 1.08–1.36; p = 0.001).Conclusion This study suggests a CDS intervention which respects the CDS Five Rights and incorporates user-centered design can affect tobacco use rates. Future work should expand the target population of this CDS tool and continue a user-centered, iterative design process.
Keywords: tobacco cessation; clinical decision support; physician; primary care; user-centered design; workflow